Pete the cat ebook Rocking field day. - Dean, James (I Can Read, Level 1: Pete the Cat., 2021)
From New York Times bestselling author-illustrator team Kimberly and James Dean comes a brand new I Can Read book in which Pete and his friends compete in Field Day! Ready, set, groove! It's field day and Pete is excited for a day filled with fun activities, like the water-balloon toss, three-legged race, an obstacle course, and tug-of-war! Join Pete the Cat and his friends Callie, Grumpy Toad, and Gus as they compete for a medal on field day! Pete the Cat: Rocking Field Day is a Guided Reading Level J and a Level One I Can Read, which means it's perfect for children learning to sound out words and sentences. Whether shared at home or in a classroom, the short sentences, familiar words, and simple concepts of Level One books support success for children eager to start reading on their own.